Pedagogika potoczności jako podstawa alternatywnej teorii nauczania o Holokauście - Kaźmierczak, Marek; Boroń, Aleksandra (Kultura-Społeczeństwo-Edukacja, 2013)
The pedagogy of commonness might be the art of distinguishing between complementary knowledge and its appearances and communicative masks. Ignorance can create some myths of daily life that sanction mistakes, abuses and misunderstandings as the equivalents or even substitutes of knowledge based on true research, dialogue and exchange of thoughts and ideas. The main thesis of this article is: commonness will not cease – that is why the future reception of the Holocaust depends on the critical thinking skills of people who as users of new media should know why the Holocaust is not only a word. The pedagogy of commonness should prepare every user (who is or will be interested in) of the new media to think critically about the diversity of representations of the Holocaust.